The Economic Integration of Different Ecological Zones in Southern Sumatra in the Late Colonial Period - Bambang Purwanto (Faculty of Cultural Sciences, Universitas Gadjah Mada, 1998)
So far, the development of southern Sumatra has been explained by its integration into the world market. This view ignores the local ecological conditions, that offer opportunities of the world market. This article therefore gives an overview of the local ecological situation and the changing ways the people exploited their environment.